The Function of the Deposit Insurance Corporation (LPS) as a Legal Protection Strategy for Customer Deposits Due to Bank Liquidation - Sri Anggraini Kusuma Dewi; Adam Pramana Putra (PT. Banjarese Pacific Indonesia, 2024)
This research aims to explore the role of the Deposit Insurance Corporation (LPS) in protecting customers when banks fail. The research methods used include policy analysis, case studies of failed banks, and reviews of related laws. It is hoped that the research results will provide a deeper understanding of the effectiveness of the legal protection provided by LPS to customers in the context of bank failures and the related compensation claims process. The Deposit Insurance Corporation (LPS) has a crucial role in protecting customer deposits when banks experience liquidation. In this context, LPS functions as a legal protection strategy for customer deposits held in banks. This action is important to maintain public confidence in banking amidst economic uncertainty. In response to the 1998 monetary crisis, the Indonesian government issued a policy of guaranteeing bank payments, including public deposits, through LPS. The importance of LPS is revealed when banks experience failures that have the potential to threaten the security of customer funds. In this situation, LPS guarantees the customer's refund up to a certain limit, providing the necessary financial protection. This creates a sense of security for customers and promotes banking system stability. With LPS, customers can be assured that their funds are safe even if unexpected events occur in the banking world. The role of LPS as a deposit insurance institution is inherent in the government's efforts to regulate and supervise the financial sector. LPS plays a role as the front guard in protecting customer interests, maintaining financial system stability, and preventing potential losses that could arise due to the possibility of bank failure.